2021
DOI: 10.1021/acsmedchemlett.1c00345
|View full text |Cite
|
Sign up to set email alerts
|

Structurally Optimized Potent Dual-Targeting NBTI Antibacterials with an Enhanced Bifurcated Halogen-Bonding Propensity

Abstract: We designed and synthesized an optimized library of novel bacterial topoisomerase inhibitors with p -halogenated phenyl right-hand side fragments and significantly enhanced and balanced dual-targeted DNA gyrase and topoisomerase IV activities of Staphylococcus aureus and Escherichia coli . By increasing the electron-withdrawing properties of the p -halogenated phenyl right-hand side fragment and maintaining a similar li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 36 publications
1
28
0
Order By: Relevance
“…As a continuation of this work, we also demonstrated that the inhibitory potencies of NBTIs with p -halogenated phenyl RHS fragments can be enhanced by increasing their electron-withdrawing properties as well as halogen-bonding propensities, while maintaining the same lipophilicity and approximately the same RHS size ( Table S1 , 47 , 49 , and 50 ). 41 Put differently, the flexibility provided by replacement of a bicyclic heteroaromatic RHS moiety with a monocyclic one (e.g., a halogenated phenyl) and its suitable length are crucial to establish halogen-bonding interactions with the Ala residues and result in a stronger enzyme inhibition. 38 Moreover, the replacement of triazole with pyrazole ( Figure 5 f, blue) generally leads to increased inhibitory potency.…”
Section: The Right-hand Side Moietymentioning
confidence: 99%
See 2 more Smart Citations
“…As a continuation of this work, we also demonstrated that the inhibitory potencies of NBTIs with p -halogenated phenyl RHS fragments can be enhanced by increasing their electron-withdrawing properties as well as halogen-bonding propensities, while maintaining the same lipophilicity and approximately the same RHS size ( Table S1 , 47 , 49 , and 50 ). 41 Put differently, the flexibility provided by replacement of a bicyclic heteroaromatic RHS moiety with a monocyclic one (e.g., a halogenated phenyl) and its suitable length are crucial to establish halogen-bonding interactions with the Ala residues and result in a stronger enzyme inhibition. 38 Moreover, the replacement of triazole with pyrazole ( Figure 5 f, blue) generally leads to increased inhibitory potency.…”
Section: The Right-hand Side Moietymentioning
confidence: 99%
“… (a) An E. coli topoIV protein homology model showing a predicted binding pose of an NBTI (compound 8 from Kokot et al 41 ). The topoIV enzyme and DNA are represented as cartoons (ParC subunit in green, ParE subunit in purple, DNA in orange).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous studies, we improved the antibacterial activity of our series of aminopiperidine-naphthyridine linked NBTIs comprising phalogenated phenyl RHS fragments by strengthening the halogenbonding propensity on the enzyme binding side [17,38,39]. Indeed, this structural optimization yielded NBTIs with excellent antibacterial activities and enzyme inhibitory potencies, but with notable hERG inhibition that remains a major issue.…”
Section: Nbtiss Optimization Strategymentioning
confidence: 97%
“…There have been attempts to overcome this challenge and provide a solid basis for designing new halogen-bonded structures 8,21,[26][27][28] , but accurate modelling of XBs is still not straightforward. This issue is paramount given the increased attention put on XBs and and their broad application in catalysis 19,[29][30][31][32] , material design [33][34][35] , supramolecular [36][37][38] and medicinal [39][40][41] chemistry, among other areas.…”
Section: Introductionmentioning
confidence: 99%